Industrial Waste in Poland (2010–2020): A Sectoral View Using Input-Output Models and Structural Decomposition Analysis - Gacek, Kamil (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
This study examines the evolution of industrial waste generation within the Polish economy over the decade of 2010–2020. Rapid economic growth, structural shifts among sectors, and growing environmental awareness have influenced waste production patterns. While numerous studies have addressed related topics in other contexts, a gap remains in assessing how technological changes and shifts in final demand jointly shape industrial waste generation in Poland. The article aims to investigate how changes in technology and final demand affected the volume and composition of waste in the Polish economy, thereby providing insights for policymakers and stakeholders seeking to enhance sustainability and resource efficiency. The research uses Environmental Extended Input-Output (EEIO) models combined with Structural Decomposition Analysis (SDA). Using Input-Output tables for Poland from 2010 and 2020 along with waste generation data aggregated into 17 sectoral clusters, the study decomposes changes in waste output into waste intensity, technological shifts, and final demand components. Further disaggregation captures the effects of product-mix adjustments, changes in demand composition, and sector-specific technological innovations. Results show that final demand is the dominant driver of increased waste generation. Technological changes produced mixed effects across sectors: the Electricity, Gas, Steam and Air Conditioning Supply sector recorded the largest reduction in waste generation, while the Waste Collection, Treatment and Disposal Activities; Materials Recovery sector experienced a significant increase. Additionally, Mining and Quarrying along with Construction played key roles, with the former undergoing notable technology-driven shifts, and the latter influenced by adjustments in both technology and final demand. These insights provide policymakers with a valuable reference for targeted waste reduction strategies while enhancing the understanding of how economic dynamics and technological progress shape environmental sustainability.